Suberin Goes Genomics: Use of a Short Living Plant to Investigate a Long Lasting Polymer - Franke, Rochus B.; Dombrink, Isabel; Schreiber, Lukas (Frontiers in Plant Science, 2012)
Suberin is a highly persistent cell wall polymer, predominantly composed of long-chain hydroxylated fatty acids. Apoplastic suberin depositions occur in internal and peripheral dermal tissues where they generate lipophilic barriers preventing uncontrolled flow of water, gases and ions. In addition, suberization provides resistance to environmental stress conditions. Despite this physiological importance the knowledge about suberin formation has increased slowly for decades. Lately, the chemical characterization of suberin in Arabidopsis enabled the proposal of genes required for suberin biosynthesis such as β-ketoacyl-CoA synthases (KCS) for fatty acid elongation and cytochrome P450 oxygenases (CYP) for fatty acid hydroxylation. Advantaged by the Arabidopsis moleculargenetic resources the in silico expression pattern of candidate genes, concerted with the tissue-specific distribution of suberin in Arabidopsis, led to the identification of suberin involved genes including KCS2, CYP86A1 and CYP86B1. The isolation of mutants with a modified suberin composition facilitated physiological studies revealing that the strong reduction in suberin in cyp86a1 mutants results in increased root water and solute permeabilities. The enhanced suberin 1 mutant, characterized by two-fold increased root suberin content, has increased water-use efficiency and is affected in mineral ion uptake and transport. In this review the most recent findings on the biosynthesis and physiological importance of suberin in Arabidopsis are summarized and discussed.